2016
DOI: 10.1116/1.4953029
|View full text |Cite
|
Sign up to set email alerts
|

Structural and chemical analysis of annealed plasma-enhanced atomic layer deposition aluminum nitride films

Abstract: Structural and chemical analysis of annealed plasma-enhanced atomic layer deposition aluminum nitride films Broas, Mikael; Sippola, Perttu; Sajavaara, Timo; Vuorinen, Vesa; Perros, Alexander Pyymaki; Lipsanen, Harri; Paulasto-Kröckel, Mervi Broas, M., Sippola, P., Sajavaara, T., Vuorinen, V., Perros, A. P., Lipsanen, H., & Paulasto-Kröckel, M. (2016). Structural and chemical analysis of annealed plasmaenhanced atomic layer deposition aluminum nitride films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 49 publications
(70 reference statements)
2
45
0
Order By: Relevance
“…143 Interestingly, these values are comparable with those shown for PECVD SiN in Table I and are consistent with the results of other PEALD AlN investigations where films with mass densities of 2.0-2.8 g/cm 3 and hydrogen contents of 13-27% have been reported. [157][158][159] Bosund in particular has previously shown that PEALD AlN hydrogen content and mass density are both a strong function of growth temperature and nitrodizing plasma time with hydrogen content decreasing with increasing temperature and plasma time, while mass density shows the opposite dependence.…”
Section: Elemental Composition-mentioning
confidence: 99%
See 1 more Smart Citation
“…143 Interestingly, these values are comparable with those shown for PECVD SiN in Table I and are consistent with the results of other PEALD AlN investigations where films with mass densities of 2.0-2.8 g/cm 3 and hydrogen contents of 13-27% have been reported. [157][158][159] Bosund in particular has previously shown that PEALD AlN hydrogen content and mass density are both a strong function of growth temperature and nitrodizing plasma time with hydrogen content decreasing with increasing temperature and plasma time, while mass density shows the opposite dependence.…”
Section: Elemental Composition-mentioning
confidence: 99%
“…[157][158][159] However, Motamedi has recently reported the growth of Al-rich PEALD AlN films. 160,161 This difference may be due to the use of a N 2 -5% H 2 plasma versus the NH 3 plasma utilized in the Bosund study or due to differences in the two techniques utilized to measure the elemental composition (surface-sensitive X-ray photoelectron spectroscopy (XPS) was used by Motamedi versus bulk-sensitive RBS for Bosund and other studies [157][158][159] ). In either case, the nitrogen-rich stoichiometry and presence of significant amounts of hydrogen detected for the PEALD AlN film in this study suggests the excess nitrogen may be incorporated primarily as NH x groups.…”
Section: Elemental Composition-mentioning
confidence: 99%
“…33 On the contrary, the PEALD samples had density values close to values reported for amorphous or polycrystalline PEALD AlN films (2.5-2.8 g/cm 3 ). 7,24,25 The nanoscale roughness results showed PEALD films to be slightly smoother compared to sputtered films. The slightly higher average roughness of the sputtered films could be attributed to the crystalline or polycrystalline structure of the film (see Sec.…”
Section: A Thickness Density and Roughnessmentioning
confidence: 98%
“…Therefore, AlN has been grown with several deposition methods, such as sputter deposition, 3 metalorganic chemical vapor deposition, 4 molecular beam epitaxy, 5 plasma enhanced chemical vapor deposition, 6 and plasma enhanced atomic layer deposition (PEALD). 7,8 Despite this, there is a lack of systematic comparison between the two main thin film deposition types: physical vapor deposition (PVD) and chemical vapor deposition (CVD) methods of AlN. Specifically, the comparative mechanical performances of the films made with these methods have not attracted much academic attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation